2017
DOI: 10.3127/ajis.v21i0.1488
|View full text |Cite
|
Sign up to set email alerts
|

Factors driving employee participation in corporate BYOD programs: A cross-national comparison from the perspective of future employees

Abstract: As individuals all around the world increasingly use mobile devices in their daily life, their desire to use the same devices in the workplace continuously grows. In response, organizations are more and more allowing their employees to use their own devices for both business and private purposes and offer so called 'Bring-your-own-Device' (BYOD) programs. For organizations with global operations there is a need to examine the drivers of BYOD demand across different national cultures to assess how to develop a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The ease and comfort in relation to the use of a system are referred to as effort expectancy (Venkatesh et al, 2003). Several studies have shown that effort expectancy is positively related to behavioural intention (Awwad & Al-Majali, 2015;Khalilzadeh et al, 2017;Wang et al, 2017). Therefore, it is hypothesized that:…”
Section: Effort Expectancymentioning
confidence: 99%
“…The ease and comfort in relation to the use of a system are referred to as effort expectancy (Venkatesh et al, 2003). Several studies have shown that effort expectancy is positively related to behavioural intention (Awwad & Al-Majali, 2015;Khalilzadeh et al, 2017;Wang et al, 2017). Therefore, it is hypothesized that:…”
Section: Effort Expectancymentioning
confidence: 99%
“…1. Quantitative empirical studies focused on people's intention to use BYOD, 20,21,23,24 its antecedents and factors of its adoption and for employee participation in BYOD programs, 3,6,16,21,[25][26][27][28][29][30][31] factors affecting work-to-life conflict, 32 its impact on learning behavior and wellbeing, 33 factors of compliance with BYOD policies, including security, organization encouragement for 'dual use' of both personal and companyprovided devices, 24,[34][35][36][37] and other consequence for security, privacy and legal aspects. 38 However, none of the studies reviewed attempted to empirically investigate the consequences of BYOD adoption on perceived job performance and work motivation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A growing number of studies have called for research to contribute a greater understanding of the consquences of BYOD use, 6,10,[14][15][16][17][18][19][20][21][22] and so this study contributes a theoretical understanding of the impact of BYOD use on a number of work-related variables. As BYOD is but one example of technology resource provided to workers, and as the core tenet of the JD-R relates to the balance between the demands placed on workers and the resources made available to them, this study then suggests the efficacy of using the JD-R model more broadly in information systems scholarship to explain work outcomes for a wide range of technologies.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful BYOD implementation depends on usability from the employee's perspective [13][14][15]. Furthermore, employees admitted to actively exploiting loopholes when they disagreed with BYOD security policies or had trouble in using applied security methods [16][17][18]. The importance of end users must be prioritised, as they determine and maintain the most control over the success of BYOD security frameworks.…”
Section: Introductionmentioning
confidence: 99%